Anticipated responses to a hypothetical minimum price for cigarettes and roll-your-own tobacco: an online cross-sectional survey with cigarette smokers and ex-smokers in the UK. Issue 3 (22nd March 2021) - Critchlow, Nathan; Moodie, Crawford; Best, Catherine; Stead, Martine
Abstract : Objectives: As tobacco companies can circumvent tax increases, a minimum retail price per-cigarette/per-gram of roll-your-own tobacco presents an additional mechanism for governments to reduce smoking. We examined (1) anticipated responses to a hypothetical minimum price-per-cigarette/per-gram among smokers in the UK; (2) what demographic and smoker characteristics are associated with anticipated responses; and (3) whether minimum pricing may help ex-smokers stay quit. Design: Cross-sectional survey (May–July 2019). Setting: UK. Participants: Adult cigarette smokers (n=2412) and ex-smokers (n=700). Main outcome measurements: Anticipated responses to a hypothetical minimum price of £10.00 for 20 cigarettes (£0.50 per-cigarette) and £13.50 for 30 grams of roll-your-own tobacco (£0.45 per-gram); approximately £0.10 per-cigarette/per-gram increases on the cheapest prices in leading UK supermarkets (January 2019). Smokers were presented with ten options (eg, ' Try to quit ') and asked which they would do ( Yes/No ) and then which they would most likely do. Ex-smokers were asked to what extent the minimum prices would help them stay quit ( A lot vs Lesser agreement ). Results: Among smokers, 55.6% said they would most likely smoke the same amount, 10.7% they would smoke less, 9.5% they would try to quit and 5.8% they would use e-cigarettes more often. Anticipated reactions were associated with demography and smoker characteristics, for example, C2DE (lower social grade) smokers were less likely than ABC1 (higher social grade) smokers to say they would smoke the same as they do now (ORAdj =0.74, 95% CI 0.62 to 0.88). Among ex-smokers, 38.5% said the minimum prices would help them stay quit 'A lot', more so among C2DE than ABC1 participants (ORAdj =1.80, 95% CI 1.30 to 2.49). Conclusions: In response to a hypothetical minimum price for cigarettes and roll-your-own tobacco, approximately a fifth of smokers in the UK indicated they would smoke less or quit and almost two-fifths of ex-smokers indicated the prices would help them stay quit.